Microwave-induced heavy metal removal from dewatered biosolids for cost-effective composting. (20th December 2019) - Li, Simeng; Li, Runwei; Tang, Youneng; Chen, Gang
Abstract: Urbanization and population growth have resulted in the accumulation of heavy metals in biosolids, and these metals act as potent environmental contaminants. In this study, a novel microwave-mediated method of extracting heavy metals from dewatered biosolids was developed. With an electromagnetic power of 140 W for a contact time of 10 s, microwave irradiation effectively induced the immobilization of heavy metals. The treated biosolids were subsequently mixed with acetic acid, sulfuric acid, or ethylenediaminetetraacetic acid (EDTA) for heavy metal extraction. The biosolids in this study were contaminated by different heavy metals, including Cd, Cu, Fe, Pb, Ni, and Zn. Among them, the concentrations of Cd (94.3 ± 14.2 mg/kg) and Pb (888.7 ± 79.8 mg/kg) were considerably above the limits allowed for land application. Conventional extraction methods were found to be insufficient in lowering heavy metal contents below regulation limits, while the microwave-mediated method efficiently increased heavy metal removal by as much as ∼3x. After the biosolids were treated, Cd and Pb concentrations decreased to 80.2 ± 2.7 and 159.8 ± 22.1 mg/kg, respectively. The treated biosolids and their products were eligible for land application as an alternative treatment. The microwave-mediated method also lowered the demand for extractants. Using a reduced concentration of sulfuric acid, acetic acid, or EDTA, at least 90% of Cu, 70% of Zn and Pb, 45% of Fe, and 20% of Ni were simultaneously removed from the contaminated biosolids. Cost analyses revealed that the microwave-mediated method could decrease the net total cost of biosolid handling by as much as 62.7%. Considering its simplicity, cost-effectiveness, and minimal environmental impacts, the proposed method offers a promising solution to the problem of heavy metal accumulation in biosolids. Graphical abstract: Image 1 Highlights: Release of heavy metals from biosolids was stimulated by microwave irradiation. Microwave mediation induced a threefold increase in lead removal from biosolids. Metals loads were low enough for land application after microwave treatment. Low-moisture biosolids had lower metal removal despite less microwave attenuation. Microwave treatment reduced the net total cost of biosolid handling by up to 62.7%.